STUDI EKPERIMENTAL RESPON INTENSITAS HUJAN DAN TEKANAN AIR PORI TANAH PENGARUHNYA TERHADAP KERUNTUHAN LERENG - Nofrizal Nofrizal; Septiwila Zarinda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Malalak is one of the youngest sub-districts in Agam Regency, the district was previously included in the administration of the district IV koto. Malalak sub-district officially separated its elf into its own sub-district on May 24, 2007. Simalaka Road (Sicincin-Malalak-Balingka) connects between Balingka nagari in district IV Koto, Malalak nagari in Malalak sub-district, and Tandikek nagari, Patamuan, Sicincin in Padang Pariaman district.This study is classified into applied research. will use soil parameter and rainfal to find out, and analyze the extent of rain characteristics on slope collapse, as well as compare the safe factors obtained using fellenius medote and Geo-studio V Software, due to disturbed soil stability or slope building rocks.In determining the value dari the safety factor of the slope by using software Geo-Slope /W obtained the value of safety factor is 0.70. The result of vibrational influence as well as the frequent rain stability of the slopes experienced a considerable decrease in the safety value of the slopes and showed that the slope conditions unstable. Analisis safety factor from research conducted on malalak road section KM 31 can be summed up a few things as follows. From the analysis obtained a definition of the factors that cause slope unstableness. From the calculation results can be that rainwater infiltration is very influential to the stability of the slope, where safety factors or FK (Safety Factor) slopes decrease along with the length of rainwater infiltration that occurs in the area especially during the soil hoarding process occurs, this can be seen from the results of geostudio analysis and fellenius method that shows reduced slope safety factors.